Investigation of the effect of Mg(OEt)2 manipulation on the ethylene and 1-butene co-polymerization performance of Ziegler-Natta catalysts. Issue 7 (3rd July 2021) - Jandaghian, Mohammad Hossein; Maddah, Yasaman; Nikzinat, Ehsan; Masoori, Maryam; Sepahi, Abdolhannan; Rashedi, Reza; Houshmandmoayed, Saeed; Davand, Razieh; Afzali, Kamal
Abstract: Although Ziegler-Natta catalysts were discovered more than four decades ago, many aspects of their characteristics are not fully understood. The effect of the support particle size on the final properties and performance of these catalysts is one of them. In this article, we present the effect of milling and heat-treating the Mg(OEt)2 support on the properties of the final catalysts and subsequently the resulting co-polymer powders. It was found that while the support milling has no significant effect on the elemental analysis results of the catalysts, the catalysts made by the milled and not-milled supports show a clear difference between the activity, particle size, and particle size distribution of the catalysts. On the other hand, the morphology of the catalyst pores is very sensitive to support manipulation, and bottleneck-type pores are predominant in the catalysts made by the nonmanipulated supports. Finally, it was found that the incorporation and the distribution of co-monomers in the final polymer chains depend on the manipulation of the raw support, and the use of milled and heat-treated supports results in the formation of co-monomer-sensitive catalysts. GRAPHICAL ABSTRACT: UF0001